Youth extracurricular activities and the importance of social skills for supervisors - Vasilios D. Kosteas (IZA World of Labor, 2022)
Youth participation in extracurricular activities is associated with a variety of benefits, ranging from higher concurrent academic performance to better labor market outcomes. In particular, these activities provide avenues through which youth can develop the interpersonal and leadership skills that are crucial to succeed as a manager. A lack of opportunity to participate in extracurricular activities for many youths, particularly those from lower-income backgrounds, may have negative consequences for developing the next generation of managers and business leaders.
Keywords: M54; J13; 330; noncognitive skills; extracurricular activities; supervisors